The Arg753Gln Polymorphism of Toll-Like Receptor 2 Has a Lower Occurrence in Patients with Syphilis, Suggesting Its Protective Effect in Czech and Slovak Individuals - Grillová, Linda; Musilová, Jana; Janečková, Klára; Pospíšilová, Petra; Kuklová, Ivana; Woznicová, Vladana; Zákoucká, Hana; Šmajs, David (Infection and immunity, 2020)
Syphilis is a bacterial infection caused by Treponema pallidum subsp. pallidum Infection with T. pallidum subsp. pallidum and its dissemination lead to the synthesis of proinflammatory cytokines triggered by the interaction of bacterial lipoproteins with Toll-like receptor 2 (TLR2). TLR2 contains several nonsynonymous single-nucleotide polymorphisms that may impact the activation of its signaling cascade and alter the responsiveness to, or the course of, various infectious diseases, including those caused by pathogenic spirochetes. To investigate whether TLR2 polymorphism may influence susceptibility to syphilis, 221 healthy individuals with no history of syphilis (controls) and 137 patients diagnosed with syphilis (cases) were screened for the presence of the Arg753Gln polymorphism in the TLR2 gene (2258G→A; rs5743708). The Arg753Gln variant occurs at a significantly lower frequency in syphilis patients (4 of 137 [3%]) than in controls (24 of 221 [10.9%]). These data suggest that TLR2 Arg753Gln may protect from the development of syphilis due to reduced signaling.
Keywords: alely; Amino Acid Substitution; Polymorphism, Single Nucleotide; Humans; syfilis; Case-Control Studies; lidé středního věku; case-control study; studie případů a kontrol; Toll-Like Receptor 2; jednonukleotidový polymorfismus; mladý dospělý; dospělí; frekvence genu; Alleles; Genotype; lidé; Slovakia; Slovenská republika; Arg753Gln polymorphism; Treponema pallidum subsp. pallidum; Adult; Toll-like receptor 2; Male; substituce aminokyselin; Middle Aged; Adolescent; toll-like receptor 2; genetická predispozice k nemoci; Genetic Predisposition to Disease; Czech Republic; Gene Frequency; Syphilis; Young Adult; genotyp; Česká republika; mužské pohlaví; mladiství